The Effect of Unemployment and Investment Levels on Economic Growth in the Province of Bangka Belitung Islands, 2015-2019 - Reniati Reniati; Mohd Fauzi Kamarudin; Rulyanti Susi Wardhani; Muhammad Faisal Akbar (Universitas Negeri Malang, 2020)
Abstract The purpose of this study was to analyze the effect of unemployment and investment on economic growth in Bangka Belitung Archipelago Province in 2015-2019. This study uses secondary data types with panel data structure at the Regency / City level in the Bangka Belitung Islands Province. In choosing the best method, this research also perform Hausman testing and Breuch Pagan LM testing to select the best alternative method in three models which have been proposed, namely fixed effect, random effect and Pooled OLS. The results showed that unemployment rate is not significantly influence economic growth in the province of Bangka Belitung Archipelago in period 2015-2019, in contrast investing rate has a significantly positive effect on economic growth in the Bangka Belitung Archipelago Province in period 2015-2019. So to increase economic growth, it is necessary to enhance investment in the Bangka Belitung Islands Province.